Safety and Efficacy Results of a Phase I, Open-Label Study of Concurrent and Delayed Nivolumab in Combination With nab-Paclitaxel and Carboplatin in Advanced Non-small Cell Lung Cancer - Goldman, Jonathan W.; Waterhouse, David M.; George, Ben; O'Dwyer, Peter J.; Bhore, Rafia; Banerjee, Sibabrata; Lyons, Larry; Louis, Chrystal U.; Ong, Teng Jin; Kelly, Karen (Frontiers in Oncology, 2019)
Introduction: Multicenter, phase I study of concurrent and delayed nivolumab plus nab-paclitaxel/carboplatin in advanced non-small cell lung cancer (NSCLC). Methods: Chemotherapy-naive patients with advanced NSCLC (ineligible for potentially curative radiation or surgery) received nab-paclitaxel 100 mg/m2 (days 1, 8, 15) and carboplatin area under the curve 6 (day 1) intravenously every 21 days (first 4 cycles); nivolumab 5 mg/kg was administered intravenously (day 15) beginning in cycle 1 (concurrent) or cycle 3 (delayed) in separate cohorts and continued beyond the 4 chemotherapy cycles. The primary objective was to assess safety. Secondary objectives were to assess tolerability and explore antitumor activity. Results: All 32 patients received chemotherapy; 20 of 22 and 6 of 10 patients also received concurrent or delayed nivolumab, respectively. No dose-limiting toxicities were reported in the concurrent cohort; 1 dose-limiting toxicity was reported in the delayed cohort. In the concurrent cohort, 20 patients (91%) had ≥1 grade 3/4 treatment-emergent adverse event (TEAE), and 7 (32%) discontinued treatment due to TEAEs. In the delayed cohort, all patients had ≥1 grade 3/4 TEAE, and 2 (20%) discontinued due to TEAEs. The median progression-free and overall survival, respectively, were 10.5 and 29.3 months in the concurrent cohort and 4.1 and 8.2 months in the delayed cohort. Conclusions: The safety profile of the combination was consistent with that of individual agents and generally similar in the 2 cohorts. Efficacy outcomes in the concurrent cohort, but not in the delayed cohort, were encouraging and support the rationale for concurrent administration of nivolumab with nab-paclitaxel/carboplatin for the treatment of advanced NSCLC.